Risk and Protective Factors for Probation Success Among Youth Offenders in Singapore - Li, Dongdong (Youth violence and juvenile justice, 2019)
The study examined the risk and protective factors for the successful completion of probation orders among youth offenders in Singapore. Specifically, we proposed a typology whereby a predictor can be labeled as a promotive factor, hazard factor, or mixed factor in a direct relationship; or a booster factor or buffering factor in an interactive relationship. This study included 701 youth offenders. Retrospective case file coding was conducted to score the Youth Level of Service/Case Management Inventory (YLS/CMI) and Structured Assessment of Protective Factors for Violence Risk-Youth Version (SAPROF-YV). Most SAPROF factors were shown to be mixed protective factors, whereas most YLS/CMI domains were either mixed risk factors or hazard factors. An absence of a supportive external pedagogical climate (PC) was the strongest mixed factor. For youth with high PC, significant booster factors included high levels of attitudes toward agreements and conditions, motivation for treatment, perseverance, and bonding to school/work, as well as low levels of risk in peer relations and education/employment. For youth with limited PC, buffering factors with the strongest effects include self-control, future orientation, and school/work. Implications for practice and future research were discussed.